2004
DOI: 10.1111/j.1600-0854.2005.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Protein Kinase C‐Induced Internalization of the Dopamine Transporter is Mediated by a Clathrin‐Dependent Mechanism

Abstract: The amount of dopamine transporter (DAT) present at the cell surface is rapidly regulated by the rates of DAT internalization to endosomes and DAT recycling back to the plasma membrane. The re-distribution of the transporter from the cell surface to endosomes was induced by phorbol ester activation of protein kinase C in porcine aortic endothelial cells stably expressing the human DAT. Inhibition of DAT recycling with the carboxylic ionophore monensin also caused significant accumulation of DAT in early endoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
208
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(228 citation statements)
references
References 42 publications
20
208
0
Order By: Relevance
“…SERT expression in depleted cell lysate CHO-SERT CHO-(SERT؉Rab4) CHO-SERT CHO-(SERT؉Rab4) Co-localization of Rab4 and SERT Is Dependent on 5HT-Like the other plasma membrane proteins (48), SERT recycles through the endosomal system (34 -36). We next investigated whether SERT traversed through Rab4-containing endosomes (34,36).…”
Section: Sert Expression On Cell Membranementioning
confidence: 99%
“…SERT expression in depleted cell lysate CHO-SERT CHO-(SERT؉Rab4) CHO-SERT CHO-(SERT؉Rab4) Co-localization of Rab4 and SERT Is Dependent on 5HT-Like the other plasma membrane proteins (48), SERT recycles through the endosomal system (34 -36). We next investigated whether SERT traversed through Rab4-containing endosomes (34,36).…”
Section: Sert Expression On Cell Membranementioning
confidence: 99%
“…Numerous studies from both our laboratory (Melikian and Buckley, 1999;Loder and Melikian, 2003;Holton et al, 2005) and others (Zhu et al, 1997;Granas et al, 2003;Sorkina et al, 2005) have demonstrated a clear role for endocytic trafficking in maintaining basal DAT surface levels and mediating PKC-induced DAT downregulation. Previous results from our laboratory revealed that DAT carboxy terminal residues L591, Y593 and I595 are necessary for basal DAT endocytosis, whereas residues 587-591 (FREKL) are required for PKC-mediated DAT downregulation (Holton et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…In PC12 and HEK cell lines, DAT basally internalizes at rates of 2-3% per minute, which corresponding to a surface t 1/2 ~13 minutes (Loder and Melikian, 2003;Li et al, 2004;Boudanova, 2008). Acute PKC activation decreases DAT surface levels by increasing DAT endocytic rates (Loder and Melikian, 2003;Sorkina et al, 2005) and, in parallel, decreasing DAT recycling rates (Loder and Melikian, 2003). Recent siRNA studies suggest that both constitutive and PKC-stimulated DAT endocytosis are clathrin-mediated , and that Nedd 4-2-dependent DAT ubiquitination on amino terminal residues is also required for PKC-stimulated DAT internalization (Sorkina et al, 2006;Miranda et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In presynaptic axon terminals, CME is required for the retrieval of synaptic vesicle proteins following neurotransmitter release, and for the recycling of vesicles back to the reserve pool 7 . Also, in presynaptic terminals, protein kinase C (PKC)-induced internalization of DAT from the synapse is clathrin-and dynamin-dependent 76 . The dopamine transporter DAT is located in presynaptic terminals and facilitates dopamine re-uptake from the synaptic cleft, thereby regulating signal strength (for review see 77 ).…”
Section: Altered Cme May Contribute To Synaptic Pathologymentioning
confidence: 99%